Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) pada Pemberian Berbagai Dosis Pupuk Kandang Kotoran Sapi dan PGPR Akar Bambu - Mahdiannoor; Murjani Murjani; Isma Isma (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
Shallot is an important commodity that becomes the basic food needs of the Indonesian people. Farmers generally use chemical or inorganic fertilizers in their cultivation activities. Inorganic fertilizers can accelerate the growing period because the nutrients can be absorbed directly by the soil. However, the continuous use of inorganic fertilizers can harm the soil and the environment, then to avoid this is to switch to using organic fertilizers. Manure is one of the organic fertilizers that can increase the availability of nutrients for plants. With the presence of intensive bacteria, it can accelerate the availability of nutrients. Bacteria whose role is to decompose organic matter are called PGPR. This study aims to (i) know the interactions (ii) know the single factor of cow manure (iii) know the single factor of bamboo root PGPR (iv) get the best interaction (v) get the best dose of cow manure (vi) get the best dose of bamboo root PGPR. This research was carried out in alluvial land in Tabalong District from March-June 2019. This study used a factorial randomized block design with the treatment is a dose of cow manure, namely: p1=10 t/ha, p2=20 t/ha, p3=30 t/ha, while the bamboo roots PGPR are: b1=20 ml, b2=25 ml, and b3=30 ml, so the combination is 9 treatments. The results showed that the observed variables were plant height, number of leaves, number of tubers, tuber diameter and tuber weight only affected plant height with a single factor treatment of cow manure and the best dose was 20 t/ha.Shallot is an important commodity that becomes the basic food needs of the Indonesian people. Farmers generally use chemical or inorganic fertilizers in their cultivation activities. Inorganic fertilizers can accelerate the growing period because the nutrients can be absorbed directly by the soil. However, the continuous use of inorganic fertilizers can harm the soil and the environment, then to avoid this is to switch to using organic fertilizers. Manure is one of the organic fertilizers that can increase the availability of nutrients for plants. With the presence of intensive bacteria, it can accelerate the availability of nutrients. Bacteria whose role is to decompose organic matter are called PGPR. This study aims to (i) know the interactions (ii) know the single factor of cow manure (iii) know the single factor of bamboo root PGPR (iv) get the best interaction (v) get the best dose of cow manure (vi) get the best dose of bamboo root PGPR. This research was carried out in alluvial land in Tabalong District from March-June 2019. This study used a factorial randomized block design with the treatment is a dose of cow manure, namely: p1=10 t/ha, p2=20 t/ha, p3=30 t/ha, while the bamboo roots PGPR are: b1=20 ml, b2=25 ml, and b3=30 ml, so the combination is 9 treatments. The results showed that the observed variables were plant height, number of leaves, number of tubers, tuber diameter and tuber weight only affected plant height with a single factor treatment of cow manure and the best dose was 20 t/ha.